Local Wisdom Based Science Education Games Historical Places in Bali My Proud Region Material in Elementary School - Ni Made Ari Yuli Artini; Komang Sujendra Diputra (Universitas Pendidikan Ganesha, 2025)
The problem in learning science in elementary schools is the lack of interactive learning media based on technology that suits the needs of students in the science subject. This study aims to analyze the effectiveness of using local wisdom-based science educational games. The development model of this research is ADDIE which includes the stages of analysis, design, development, implementation, and evaluation. The subjects of this study were 12 fifth grade students. The research methods and instruments used were multiple-choice tests and non-tests in the form of questionnaires. Data analysis was carried out using quantitative descriptive, qualitative descriptive, and inferential statistical approaches. The results showed that local wisdom-based science educational games obtained a feasibility score of 93.7% from material experts, 92.5% from learning design experts, and 96.6% from media experts, with very good qualifications. Individual and small group trials produced scores of 93.3% and 92.7% respectively, which were also categorized as very good. The effectiveness test with 21 students showed a tvalue of 4.93 which was greater than the ttable of 2.08 (tvalue > ttable) at a significance level of 5% (df = 20), so H0 was rejected and H1 was accepted which stated that the average post-test results of students were more than the KKTP value. So it can be concluded that the local wisdom-based science education games of historical places in Bali have proven effective for use in the material of my proud region in grade V of elementary school.